Preparation method and preparation device of composite conductor material
By using iron-carbon alloy to treat the cracking product of carbon source gas on the surface of the metal matrix, carbon impurities are reduced, and the conductivity and thermal conductivity of graphene are improved, and the problem of a lot of carbon impurities in traditional methods is solved.
Patent Information
- Application Number
- CN202310871031.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
Smart Images

Figure CN119307883A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductor materials, and in particular to a preparation method and a preparation device of a composite conductor material. Background Art
[0002] Copper and copper alloys are often used as contact materials for electrical contact components such as switches, plugs, and relays due to their excellent electrical conductivity, ductility, and corrosion resistance. The opening and closing of electrical contact components are achieved through the connection and disconnection of contacts. As the performance requirements for contacts become higher and higher, various surface treatments are often performed on copper or copper alloys to meet the requirements of contact materials.
[0003] Graphene has excellent mechanical, electrical and thermal conductivity properties, such as a bandgap of almost zero, very high carrier mobility and a large specific surface area. These properties enable graphene to significantly improve the conductivity and other properties of metals such as copper and copper alloys.
[0004] In the mass production process of traditional metal-based graphene materials, in order to ensure the overall quality of the produced metal-based graphene materials, a large flow of gas-phase carbon source and carrier gas needs to be provided. In actual industrial production, a large flow of gas-phase carbon source such as methane will be cracked into a large amount of insufficiently cracked substances during the initial cracking process. The insufficiently cracked substances react quickly with the metal, resulting in the prepared metal-based graphene materials with more carbon impurities, small graphene crystal domains, and more grain boundaries, which cannot effectively improve the electrical conductivity and thermal conductivity of the metal matrix. Summary of the invention
[0005] In view of this, the present application provides a method and device for preparing a composite conductor material, aiming to improve the problem that the prior art for preparing metal-based graphene materials cannot effectively improve the electrical conductivity and thermal conductivity of the metal matrix.
[0006] The embodiment of the present application is implemented as follows: a method for preparing a composite conductor material, comprising: providing a carbon source gas and an iron-carbon alloy, heating to a first temperature T1, maintaining the temperature for a period of time t1, cracking the carbon source gas to obtain a cracking product, and treating the cracking product with the iron-carbon alloy to obtain an intermediate gas;
[0007] A metal substrate is provided, and the metal substrate is placed in the intermediate gas, heated to a second temperature T2, kept at the temperature for a period of time t2, and graphene is grown on the surface of the metal substrate to obtain a composite conductor material.
[0008] Optionally, in some embodiments of the present application, the carbon source gas includes one or more of methane, ethylene, and acetylene; and / or
[0009] The volume flow rate of the carbon source gas is 200 sccm to 250 sccm.
[0010] Optionally, in some embodiments of the present application, the iron-carbon alloy includes one or more of stainless steel, low carbon steel, and low alloy steel.
[0011] Optionally, in some embodiments of the present application, the material of the metal matrix is a metal single substance or an alloy, the metal single substance includes copper and nickel, and the alloy includes a copper-nickel alloy; and / or
[0012] The metal matrix is metal powder, and the average particle size of the metal powder is 0.01 μm to 100 μm.
[0013] Optionally, in some embodiments of the present application, the intermediate gas includes C x H y One or more of the following, where 1≤x≤2, 0≤y≤4.
[0014] Optionally, in some embodiments of the present application, the first temperature T1 is 800° C. to 1020° C.; and / or
[0015] The heating rate of heating to the first temperature T1 is 10°C / min to 20°C / min; and / or
[0016] The time t1 is 20s to 180s.
[0017] Optionally, in some embodiments of the present application, the second temperature T2 is 950° C. to 1070° C.; and / or
[0018] The heating rate of heating to the second temperature T2 is 10°C / min to 20°C / min; and / or
[0019] The time t2 is 1.5h to 2h.
[0020] Optionally, in some embodiments of the present application, the carbon source gas also includes a carrier gas, and the carrier gas includes one or more of hydrogen, ammonia, and nitrogen; the volume flow rate of the carrier gas is 800 sccm to 1000 sccm.
[0021] Optionally, in some embodiments of the present application, providing a metal matrix also includes providing an anti-sintering agent, and the anti-sintering agent includes one or more of magnesium oxide, aluminum oxide, graphite, chromium, and silver; the anti-sintering agent is an anti-sintering agent powder, and the average particle size of the anti-sintering agent powder is 0.1μm to 15μm; the mass ratio of the metal matrix and the anti-sintering agent is (5 to 10):4.
[0022] Optionally, in some embodiments of the present application, the iron-carbon alloy is used to treat the cracking product in a first inert atmosphere, and the pressure of the first inert atmosphere is 100 kPa to 103 kPa; the volume flow rate of the inert gas in the first inert atmosphere is 700 sccm to 1000 sccm; the inert gas in the first inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon; and / or
[0023] The growth of graphene on the surface of the metal substrate is carried out in a second inert atmosphere, and the pressure of the second inert atmosphere is 100kPa~103kPa; the volume flow rate of the inert gas in the second inert atmosphere is 700sccm~1000sccm; the inert gas in the second inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon.
[0024] Accordingly, the present application also provides a preparation device for implementing the above-mentioned preparation method, comprising:
[0025] The first reaction chamber contains an iron-carbon alloy, the second reaction chamber contains a metal matrix, and the iron-carbon alloy is structurally connected so that the carbon source gas can pass into the second reaction chamber after reacting with the iron-carbon alloy to react with the metal matrix.
[0026] Optionally, in some embodiments of the present application, the preparation apparatus further comprises a gas input device located upstream of the first reaction chamber, for inputting a carbon source gas.
[0027] Optionally, in some embodiments of the present application, along the horizontal direction, the first reaction chamber and the second reaction chamber have a left-right structure, and the iron-carbon alloy is filled in the first reaction chamber.
[0028] Optionally, in some embodiments of the present application, the first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a filled filler-like iron-carbon alloy, the particle size of the filler-like iron-carbon alloy is 50 mesh to 400 mesh, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
[0029] Optionally, in some embodiments of the present application, the first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a stacked tubular iron-carbon alloy, the inner diameter of the tubular iron-carbon alloy is 50μm to 100mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
[0030] Optionally, in some embodiments of the present application, the first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a plate-shaped iron-carbon alloy placed at intervals, the spacing between adjacent plate-shaped iron-carbon alloys is 1 mm to 100 mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
[0031] Optionally, in some embodiments of the present application, the first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a mesh iron-carbon alloy, the mesh size of the mesh iron-carbon alloy is 50μm~100mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
[0032] Optionally, in some embodiments of the present application, along the vertical direction, the first reaction chamber and the second reaction chamber have an up-and-down structure.
[0033] Optionally, in some embodiments of the present application, the first reaction chamber is located on the upper side of the second reaction chamber, the iron-carbon alloy is a cover plate with holes on the plate surface, the second reaction chamber has an opening, the iron-carbon alloy covers the opening, and the carbon source gas is introduced from the side of the iron-carbon alloy away from the second reaction chamber.
[0034] Optionally, in some embodiments of the present application, the first reaction chamber and the second reaction chamber have an internal and external structure, the absolute value of the difference in inner diameter between the first reaction chamber and the second reaction chamber is ≥5 mm, the iron-carbon alloy is tubular, and the wall thickness of the iron-carbon alloy is 3 mm to 9 mm.
[0035] Optionally, in some embodiments of the present application, the first reaction chamber is located inside the second reaction chamber, the iron-carbon alloy is located in the second reaction chamber, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the end face of the iron-carbon alloy.
[0036] Optionally, in some embodiments of the present application, the first reaction chamber is located outside the second reaction chamber, the iron-carbon alloy is located inside the first reaction chamber, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the outer side of the iron-carbon alloy away from the second reaction chamber.
[0037] The preparation method of the composite conductor material described in the present application firstly heats the carbon source gas to cause preliminary cracking to generate cracking products, wherein the cracking products include insufficiently cracked substances and fully cracked substances, and after the cracking products contact the iron-carbon alloy, most of the insufficiently cracked substances can react with the iron-carbon alloy and be absorbed, so that a buffer time can be reserved for the sufficient cracking of the carbon source gas, and then the intermediate gas is further cracked at the temperature T2 and reacts with the metal matrix, and graphene is grown on the surface of the metal matrix through vapor deposition. In this way, the iron-carbon alloy is first used to remove most of the insufficiently cracked substances, and the carbon is fully cracked faster on the surface of the metal matrix to form carbon, and then graphene is deposited, which can effectively reduce the content of carbon impurities (i.e., insufficiently cracked substances) in the composite conductor material, and can make the prepared graphene have larger crystal domains and fewer grain boundaries, which is conducive to preparing a composite conductor material with good electrical conductivity and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0039] Figure 1 is a flow chart of a method for preparing a composite conductor material provided in an embodiment of the present application;
[0040] Figure 2 is a schematic top view of a device for preparing a composite conductor material provided in an embodiment of the present application;
[0041] Figure 3 It is a schematic top view of another device for preparing a composite conductor material provided in an embodiment of the present application;
[0042] Figure 4 It is a schematic top view of another device for preparing a composite conductor material provided in an embodiment of the present application;
[0043] Figure 5 It is a schematic top view of another device for preparing a composite conductor material provided in an embodiment of the present application;
[0044] Figure 6 It is a schematic top view of another device for preparing a composite conductor material provided in an embodiment of the present application;
[0045] Figure 7 is a scanning electron microscope image of the electrical contact provided in the device embodiment 1 of the present application;
[0046] Reference numerals:
[0047] 10-iron-carbon alloy; 101-filler-shaped iron-carbon alloy; 102-net-shaped iron-carbon alloy; 103-plate-shaped iron-carbon alloy; 20-metal matrix; 30-second reaction chamber; 40-reaction furnace. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0049] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0050] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0051] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0052] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0053] The technical solution of this application is as follows:
[0054] First, as Figure 1 As shown, the present embodiment provides a method for preparing a composite conductor material, comprising:
[0055] S11, providing a carbon source gas and an iron-carbon alloy 10, raising the temperature to a first temperature T1, and maintaining the temperature for a period of time t1, so that the carbon source gas is cracked to obtain a cracking product, and the iron-carbon alloy 10 processes the cracking product to obtain an intermediate gas;
[0056] S12, providing a metal substrate 20, placing the metal substrate 20 in the intermediate gas, heating it to a second temperature T2, maintaining the temperature for a period of time t2, growing graphene on the surface of the metal substrate 20, and obtaining a composite conductor material.
[0057] It should be noted that the iron-carbon alloy 10 is a metal material that is easily combined with carbon elements. The carbon source gas will crack after being heated, and the initial cracking will generate insufficiently cracked substances such as CH3 and CH2. These insufficiently cracked substances will penetrate into the iron-carbon alloy 10. On the one hand, the insufficiently cracked substances can be removed by carburizing reaction, and a buffer time can be reserved for the sufficient cracking of the carbon source gas. On the other hand, the performance of the iron-carbon alloy 10 can be improved. It should be further explained that as the cracking time increases, the insufficiently cracked substances such as CH3 and CH2 will further crack into substances such as CH2 and CH. The metal matrix 20 is placed in the substance that undergoes initial cracking. As the temperature increases, the initially cracked substances will be more quickly and fully cracked to generate C, and C will be vapor-deposited on the metal surface to form graphene.
[0058] In the prior art, when metal-based composite materials are prepared in large quantities, the carbon source gas is cracked to produce CH3, CH2, CH and C. The substances that are not fully cracked, such as CH3, CH2, CH, etc., are deposited on the surface of the metal-based material. As a result, the prepared metal-based graphene material has a lot of carbon impurities, small graphene crystal domains, and many grain boundaries, which cannot effectively improve the electrical conductivity and thermal conductivity of the metal-based material.
[0059] The preparation method of the composite conductor material provided by the present application firstly heats the carbon source gas to undergo preliminary cracking to generate cracking products, wherein the cracking products include insufficiently cracked substances (unstable carbon source gas) and fully cracked substances (stable carbon source gas). After the cracking products come into contact with the iron-carbon alloy, most of the insufficiently cracked substances can react with the iron-carbon alloy 10 and be absorbed. In this way, a buffer time can be reserved for the sufficient cracking of the carbon source gas. Then, the intermediate gas is further cracked at the temperature T2 and reacts with the metal matrix 20. Through vapor deposition, graphene is grown on the surface of the metal matrix 20. In this way, the iron-carbon alloy 10 is first used to remove most of the insufficiently cracked substances, and the carbon is fully cracked faster on the surface of the metal matrix 20 to form carbon, and then graphene is deposited. This can effectively reduce the content of carbon impurities (i.e., insufficiently cracked substances) in the composite conductor material, and can make the prepared graphene have larger crystal domains and fewer grain boundaries, which is conducive to the preparation of a composite conductor material with good electrical conductivity and thermal conductivity.
[0060] In the S11:
[0061] In some embodiments, the carbon source gas includes one or more of methane, ethylene, and acetylene.
[0062] In some embodiments, the volume flow rate of the carbon source gas is 200 sccm to 250 sccm, for example, 205 sccm to 245 sccm, 210 sccm to 240 sccm, 215 sccm to 235 sccm, 220 sccm to 230 sccm, 225 ccm to 228 sccm, etc. Within the volume flow rate range, the carbon source gas is facilitated to fully and uniformly contact the iron-carbon alloy 10.
[0063] In some embodiments, the intermediate gas includes C x H y One or more of the following, where 1≤x≤2, 0≤y≤4.
[0064] Furthermore, the intermediate gas includes one or more of C2H3, C2H2, C2H, C2, CH3, CH2, CH, and C.
[0065] It can be understood that in some embodiments, the carbon source gas can be heated first, and then heated together with the iron-carbon alloy 10 to react. Further, the carbon source gas can be heated to 800°C to 1000°C, for example, 820°C to 980°C, 840°C to 960°C, 860°C to 950°C, 880°C to 940°C, 900°C to 920°C, etc. In this way, the reaction time of the carbon source gas and the iron-carbon alloy 10 can be shortened and the efficiency can be improved. In some embodiments, the carbon source gas provided also includes a carrier gas, and the carrier gas carries the carbon source gas.
[0066] Further, the volume flow rate of the carrier gas is 800 sccm to 1000 sccm, for example, 820 sccm to 980 sccm, 840 sccm to 960 sccm, 850 sccm to 950 sccm, 860 sccm to 940 sccm, 880 sccm to 920 sccm, etc. Within the rate range, the carrier gas can effectively carry the carbon source gas and transport the carbon source gas to react with the iron-carbon alloy 10.
[0067] In some embodiments, the carrier gas includes one or more of hydrogen, ammonia, and nitrogen.
[0068] In some embodiments, the iron-carbon alloy 10 includes one or more of stainless steel, low carbon steel, and low alloy steel.
[0069] In some embodiments, the structure of the iron-carbon alloy 10 can be a mesh, a hollow tube, a cylinder, a filler, a foam hole, etc. It can be understood that the iron-carbon alloy 10 can be a porous structure surrounded by a single porous substrate, such as the porous substrate can be a stainless steel plate, and the iron-carbon alloy 10 is a structure in which the stainless steel plates are stacked at intervals.
[0070] In some embodiments, the first temperature T1 is 800°C to 1020°C, for example, 820°C to 980°C, 840°C to 960°C, 860°C to 940°C, 880°C to 920°C, 890°C to 910°C, etc.
[0071] In some embodiments, the heating rate to the first temperature T1 is 10°C / min to 20°C / min, for example, 11°C / min to 19°C / min, 12°C / min to 18°C / min, 13°C / min to 17°C / min, 14°C / min to 16°C / min, etc.
[0072] In some embodiments, the time t1 is 20s to 180s, for example, 30s to 160s, 40s to 150s, 50s to 140s, 60s to 120s, 80s to 100s, etc.
[0073] In this way, under the condition that the carbon source gas reacts with the iron-carbon alloy 10, it is conducive to the carburizing reaction between the carbon source gas and the iron-carbon alloy 10, effectively removing the insufficiently cracked substances produced by the insufficient cracking of the carbon source gas, and ensuring that the sufficiently cracked carbon will not be consumed in large quantities by the iron-carbon alloy 10.
[0074] In S12:
[0075] In some embodiments, the material of the metal matrix 20 is a metal single substance or an alloy. The metal single substance includes copper and nickel, and the alloy includes a copper-nickel alloy.
[0076] In some embodiments, the metal substrate 20 is a metal powder, and the average particle size of the metal powder is 0.01 μm to 100 μm, for example, 1 μm to 90 μm, 10 μm to 80 μm, 20 μm to 70 μm, 30 μm to 60 μm, 40 μm to 50 μm, etc. Within the average particle size range, it is beneficial for the metal substrate 20 to fully contact and react with the intermediate gas, and graphene is deposited on the surface of the metal substrate 20.
[0077] In some embodiments, providing the metal matrix 20 includes: providing the metal matrix 20 and an anti-sintering agent. The anti-sintering agent is mixed with the metal matrix 20 and placed in the intermediate gas.
[0078] In some embodiments, the anti-sintering agent is an anti-sintering agent powder, and the average particle size of the anti-sintering agent powder can be 0.1μm to 15μm, for example, 1μm to 14μm, 2μm to 13μm, 3μm to 12μm, 4μm to 11μm, 5μm to 10μm, etc.
[0079] In some embodiments, the anti-sintering agent includes one or more of magnesium oxide, aluminum oxide, graphite, chromium, and silver. For example, the anti-sintering agent can be magnesium oxide, or a mixture of magnesium oxide and aluminum oxide, or a mixture of magnesium oxide, aluminum oxide, and graphite.
[0080] In some embodiments, the mass ratio of the metal substrate 20 to the anti-sintering agent is (5-10):4, for example, 6:4, 7:4, 8:4, 9:4, etc. It can be understood that the anti-sintering agent can improve the corrosion resistance and thermal shock resistance of the metal substrate 20 at high temperatures, so that the metal substrate 20 still maintains excellent corrosion resistance and other properties after high temperature reaction.
[0081] In some embodiments, the second temperature T2 is 950°C to 1070°C, for example, 960°C to 1060°C, 970°C to 1050°C, 980°C to 1040°C, 990°C to 1030°C, 1000°C to 1020°C, etc.
[0082] In some embodiments, the heating rate to the second temperature T2 is 10°C / min to 20°C / min, for example, 11°C / min to 19°C / min, 12°C / min to 18°C / min, 13°C / min to 17°C / min, 14°C / min to 16°C / min, etc.
[0083] In some embodiments, the time t2 is 1.5h to 2h, for example, it can be 1.55h to 1.95h, 1.6h to 1.9h, 1.65h to 1.85h, 1.7h to 1.8h, 1.75h to 1.78h, etc.
[0084] In this way, under the temperature range and time range conditions for the reaction between the metal substrate 20 and the intermediate gas, vapor deposition is conducive to depositing graphene on the surface of the metal substrate 20, so that the graphene effectively improves the electrical and thermal conductivity of the metal substrate 20.
[0085] It can be understood that after the heating reaction between the metal substrate 20 and the intermediate gas is completed, it also includes cooling to room temperature.
[0086] In some embodiments, the processing of the cracking product by the iron-carbon alloy is performed in a first inert atmosphere.
[0087] In some embodiments, the pressure of the first inert atmosphere is 100 kPa to 103 kPa, which is helpful to ensure that the pressure of the carburizing reaction of the iron-carbon alloy is within a suitable range, thereby promoting the carburizing reaction.
[0088] In some embodiments, the volume flow rate of the inert gas in the first inert atmosphere is 700 sccm to 1000 sccm, for example, 720 sccm to 980 sccm, 750 sccm to 950 sccm, 780 sccm to 920 sccm, 800 sccm to 900 sccm, 820 sccm to 880 sccm, etc. Within the volume flow rate range, it is beneficial to increase the pressure stably and improve safety.
[0089] In some embodiments, the inert gas in the first inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon.
[0090] In some embodiments, growing graphene on the surface of the metal substrate is performed in a second inert atmosphere.
[0091] In some embodiments, the pressure of the second inert atmosphere is 100 kPa to 103 kPa. This helps to ensure that the pressure of the metal substrate for depositing graphene is within a suitable range, thereby promoting the deposition of graphene.
[0092] In some embodiments, the volume flow rate of the inert gas in the second inert atmosphere is 700 sccm to 1000 sccm, for example, 720 sccm to 980 sccm, 750 sccm to 950 sccm, 780 sccm to 920 sccm, 800 sccm to 900 sccm, 820 sccm to 880 sccm, etc. Within the volume flow rate range, it is beneficial to ensure that the reaction pressure is within an appropriate range and promote the formation of graphene.
[0093] In some embodiments, the inert gas in the second inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon.
[0094] In a second aspect, an embodiment of the present application further provides a preparation device for implementing the above-mentioned preparation method, the preparation device comprising: a first reaction chamber and a second reaction chamber 30 connected to the first reaction chamber, the first reaction chamber contains an iron-carbon alloy, the second reaction chamber 30 contains a metal matrix, and the structure of the iron-carbon alloy is connected so that the carbon source gas can pass into the second reaction chamber 30 after reacting with the iron-carbon alloy to react with the metal matrix.
[0095] In some embodiments, the preparation apparatus further comprises a gas input device located upstream of the first reaction chamber for inputting a carbon source gas.
[0096] Specifically, when the composite conductor material is prepared using the preparation device and the preparation method, the steps include:
[0097] Providing a carbon source gas, passing it into the first reaction chamber, heating it, cracking the carbon source gas, and obtaining an intermediate gas after passing through the iron-carbon alloy 10;
[0098] The metal substrate 20 is placed in the second reaction chamber 30. After the intermediate gas enters the second reaction chamber 30, the temperature is raised to the second temperature T2 and kept at the temperature for a period of time t2. Graphene is grown on the surface of the metal substrate 20 by vapor deposition to obtain a composite conductor material.
[0099] In some embodiments, before the carbon source gas is introduced into the first reaction chamber, the method further includes: performing a non-oxidation treatment on the first reaction chamber.
[0100] It can be understood that the carbon source gas is easy to burn with oxygen to generate carbon dioxide and water in an oxygen environment, so the reaction environment needs to be treated to be non-oxidative.
[0101] In some embodiments, performing non-oxidation treatment on the first reaction chamber includes: evacuating the first reaction chamber to a first pressure and introducing an inert gas.
[0102] Furthermore, the vacuuming to the first pressure includes vacuuming to 0 kPa to 10×10 -3 kPa, for example, it can be 1×10 -3 kPa~9×10 -3 kPa, 2×10 -3 kPa~8×10 -3 kPa, 3×10 -3 kPa~7×10 -3 kPa, 4×10 - 3 kPa~6×10 -3 kPa, 5×10 -3 kPa~5.5×10 -3 kPa, etc. In this way, within the first pressure range, it is beneficial to ensure that the oxygen in the first reaction chamber is effectively removed.
[0103] In some embodiments, before the intermediate gas enters the second reaction chamber 30 , the second reaction chamber 30 is further subjected to a non-oxidation treatment.
[0104] In some embodiments, performing non-oxidation treatment on the second reaction chamber 30 includes: evacuating the second reaction chamber 30 to a second pressure and introducing an inert gas.
[0105] Furthermore, the vacuuming to the second pressure includes vacuuming to 0 kPa to 10×10 -3 kPa, for example, it can be 1×10 -3 kPa~9×10 -3 kPa, 2×10 -3 kPa~8×10 -3 kPa, 3×10 -3 kPa~7×10 -3 kPa, 4×10 - 3 kPa~6×10 -3 kPa, 5×10 -3 kPa~5.5×10 -3 kPa, etc. In this way, within the second pressure range, it is beneficial to ensure that the oxygen in the second reaction chamber 30 is effectively removed.
[0106] In some embodiments, the first reaction chamber and the second reaction chamber 30 are both located in the reaction furnace 40. In this way, the non-oxidation treatment of the first reaction chamber and the second reaction chamber 30 can be combined into a non-oxidation treatment of the third reaction chamber, and the carbon source gas reacts with the iron-carbon alloy 10 and then directly reacts with the metal matrix 20, without the need for artificial delivery of intermediate gas, making the operation more convenient.
[0107] In some embodiments, along the horizontal direction, the first reaction chamber and the second reaction chamber 30 have a left-right structure, and the iron-carbon alloy is disposed between the first reaction chamber and the second reaction chamber 30. Specifically, the iron-carbon alloy 10 can be filled in the first reaction chamber, or can be disposed on the chamber wall of the first reaction chamber.
[0108] Specifically, see Figure 2 In some embodiments, the first reaction chamber is located on the left side of the second reaction chamber 30, and the iron-carbon alloy is a filler-like iron-carbon alloy 101, and the particle size of the filler-like iron-carbon alloy 101 is 80 mesh to 380 mesh, for example, 90 mesh to 360 mesh, 100 mesh to 350 mesh, 120 mesh to 320 mesh, 150 mesh to 300 mesh, 180 mesh to 200 mesh, etc. The carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber 30.
[0109] See also Figure 3 In some other embodiments, the first reaction chamber is located on the left side of the second reaction chamber 30, and the iron-carbon alloy is a plate-shaped iron-carbon alloy 103 placed at intervals, and the spacing between adjacent plate-shaped iron-carbon alloys 103 is 1mm to 100mm, for example, 5mm to 90mm, 10mm to 20mm, 30mm to 40mm, 50mm to 60mm, 70mm to 80mm, etc. The carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber 30.
[0110] See also Figure 4 In some other embodiments, the first reaction chamber is located on the left side of the second reaction chamber 30, the iron-carbon alloy is a mesh iron-carbon alloy 102, and the mesh size of the mesh iron-carbon alloy 102 is 50 μm to 100 mm, for example, 5 mm to 90 mm, 10 mm to 20 mm, 30 mm to 40 mm, 50 mm to 60 mm, 70 mm to 80 mm, etc. The carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber 30.
[0111] In some other embodiments, the first reaction chamber is located on the left side of the second reaction chamber 30, the iron-carbon alloy is a stacked tubular iron-carbon alloy, and the inner diameter of the tubular iron-carbon alloy is 50 μm to 100 mm, for example, 5 mm to 90 mm, 10 mm to 20 mm, 30 mm to 40 mm, 50 mm to 60 mm, 70 mm to 80 mm, etc. The carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber 30.
[0112] In some embodiments, along the vertical direction, the first reaction chamber and the second reaction chamber 30 have an up-and-down structure.
[0113] Specifically, in some embodiments, the first reaction chamber is located on the upper side of the second reaction chamber 30, the iron-carbon alloy is a cover plate with holes on the plate surface, the second reaction chamber 30 has an opening, the iron-carbon alloy covers the opening, and the carbon source gas is introduced from the side of the iron-carbon alloy away from the second reaction chamber 30. It can be understood that after the carbon source gas reacts with the iron-carbon alloy 10, it overflows through the holes into the second reaction chamber 30 and contacts and reacts with the metal matrix 20. The iron-carbon alloy can be a filler-like iron-carbon alloy 101, a mesh-like iron-carbon alloy 102, or a plate-like iron-carbon alloy 103.
[0114] In some embodiments, the first reaction chamber and the second reaction chamber 30 have an inner and outer structure, and the absolute value of the inner diameter difference between the first reaction chamber and the second reaction chamber 30 is ≥5 mm. The iron-carbon alloy is tubular, and the wall thickness of the iron-carbon alloy is 3 mm to 9 mm.
[0115] Specifically, see Figure 5 In some embodiments, the first reaction chamber is located inside the second reaction chamber 30, the iron-carbon alloy is located in the second reaction chamber 30, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the end face of the iron-carbon alloy. It can be understood that after the carbon source gas reacts with the iron-carbon alloy 10, it overflows into the second reaction chamber 30 through the holes and contacts and reacts with the metal substrate 20. It can be understood that after the carbon source gas reacts with the iron-carbon alloy 10, it overflows into the second reaction chamber 30 through the holes and contacts and reacts with the metal substrate 20.
[0116] In other embodiments, the first reaction chamber is located outside the second reaction chamber, the iron-carbon alloy is located inside the first reaction chamber, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the outer side of the iron-carbon alloy away from the second reaction chamber. It can be understood that after the carbon source gas reacts with the iron-carbon alloy 10, it overflows into the second reaction chamber 30 through the holes and contacts and reacts with the metal substrate 20.
[0117] In some embodiments, the material of the second reaction chamber 30 may be quartz. Quartz is resistant to high temperatures, corrosion, and has good thermal stability, which is conducive to the deposition and preparation of graphene.
[0118] In other embodiments, the material of the second reaction chamber 30 may be an iron-carbon alloy 10. In this way, the iron-carbon alloy 10 can consume excess carbon source gas to prevent excessive carbon source content from causing graphene to agglomerate and produce graphite.
[0119] In a third aspect, an embodiment of the present application further provides a composite conductor material, which is prepared by the above-mentioned preparation method or the above-mentioned preparation device.
[0120] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0121] Example 1
[0122] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0123] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a stainless steel hollow tube is placed in the middle of the quartz boat, the stainless steel hollow tube is 5 mm smaller than the inner diameter of the quartz boat, and the quartz boat is placed into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0124] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0125] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone and are preheated to 850°C. CH4 and H2 enter the stainless steel tube from the end face of the stainless steel hollow tube and stay in the stainless steel tube for 90s. After the fully cracked substances are generated, they overflow from the holes on the side and react with the copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0126] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0127] Example 2
[0128] 5 kg of nickel powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a stainless steel hollow tube is placed in the middle of the quartz boat, the stainless steel hollow tube is 6 mm smaller than the inner diameter of the quartz boat, and the quartz boat is placed into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0129] The reaction chamber was evacuated to 9.9 x 10 -3kPa, introduce 700sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 1020℃.
[0130] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 200 sccm, and the volume flow rate of H2 is 800 sccm. CH4 and H2 enter the preheating zone and are preheated to 950°C. CH4 and H2 enter the stainless steel tube from the end face of the stainless steel hollow tube and stay in the stainless steel tube for 90 seconds. After the fully cracked substances are generated, they overflow from the holes on the side and react with the copper powder in the quartz boat. The reaction lasts for 1.5 hours, so that the surface of the nickel powder grows to form a graphene film.
[0131] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a nickel-based graphene composite material.
[0132] Example 3
[0133] Weigh 2 kg of nickel powder with a particle size of 1 μm, 3 kg of copper powder with a particle size of 1 μm, and 4 kg of magnesium oxide with a particle size of 1 μm, mix them and put them into a quartz boat, put a stainless steel hollow tube in the middle of the quartz boat, the stainless steel hollow tube is 8 mm smaller than the inner diameter of the quartz boat, and put the quartz boat into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0134] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 800sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 1000℃.
[0135] A gas source was opened to introduce CH4 and H2, wherein the volume flow rate of CH4 was 220 sccm, and the volume flow rate of H2 was 900 sccm. CH4 and H2 entered the stainless steel tube from the end face of the stainless steel hollow tube, stayed in the stainless steel tube for 90 seconds, and after fully cracked substances were generated, they overflowed from the holes on the side and reacted with copper powder and nickel powder in the quartz boat. The reaction lasted for 1.75 hours, so that the surfaces of the copper powder and the nickel powder grew to form a graphene film;
[0136] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-nickel based graphene composite material.
[0137] Example 4
[0138] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0139] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a stainless steel hollow tube is placed in the middle of the quartz boat, the stainless steel hollow tube is 5 mm smaller than the inner diameter of the quartz boat, and the quartz boat is placed into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0140] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0141] CH4 and H2 are heated to 850°C, and the heated CH4 and H2 are introduced through a gas source, wherein the volume flow rate of CH4 is 250 sccm, and the volume flow rate of H2 is 1000 sccm. CH4 and H2 enter the stainless steel tube from the end face of the stainless steel hollow tube, and stay in the stainless steel tube for 90 seconds. After fully cracked substances are generated, they overflow from the holes on the side and react with copper powder in the quartz boat. The reaction lasts for 2 hours, so that a graphene film grows on the surface of the copper powder;
[0142] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0143] Example 5
[0144] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0145] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a stainless steel hollow tube is placed in the middle of the quartz boat, the stainless steel hollow tube is 5 mm smaller than the inner diameter of the quartz boat, and the quartz boat is placed into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0146] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0147] The gas source is turned on to introduce ethylene and H2, wherein the volume flow rate of ethylene is 250sccm, and the volume flow rate of H2 is 1000sccm. Ethylene and H2 enter the preheating zone from the end face of the stainless steel hollow tube, are preheated to 850°C, enter the stainless steel tube, stay in the stainless steel tube for 90s, and after fully cracked substances are generated, they overflow from the holes on the side and react with copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0148] The ethylene and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0149] Example 6
[0150] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0151] Weigh 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm, mix them and put them into a quartz boat, put the quartz boat into the middle position of a stainless steel hollow tube, the stainless steel hollow tube is 5 mm larger than the inner diameter of the quartz boat, and put the stainless steel hollow tube into the reaction chamber of a vacuum tube furnace, wherein a hole is opened on the side of the stainless steel hollow tube;
[0152] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 800℃.
[0153] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone and are preheated to 850°C. CH4 and H2 enter the stainless steel tube from the side of the stainless steel hollow tube away from the quartz boat, stay in the stainless steel tube for 90s, and after fully cracked substances are generated, they overflow into the quartz boat from the holes on the side. The reaction chamber is further heated to 1020°C, and reacts with copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0154] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0155] Example 7
[0156] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0157] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm were weighed, mixed and loaded into a quartz boat, a mesh stainless steel with a pore size of 50 mm was provided and arranged upstream of the quartz boat, and both the mesh stainless steel and the quartz boat were located in the reaction chamber of the vacuum tube furnace;
[0158] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0159] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the mesh stainless steel from the end of the mesh stainless steel away from the quartz boat, stay in the mesh stainless steel for 90s, and after generating fully cracked substances, pass through the mesh stainless steel and react with copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0160] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0161] Example 8
[0162] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0163] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a filler-like stainless steel with a particle size of 100 mesh is provided and arranged upstream of the quartz boat, and both the filler-like stainless steel and the quartz boat are located in a reaction chamber of a vacuum tube furnace;
[0164] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0165] Open the gas source to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the packing-like stainless steel from the end of the packing-like stainless steel away from the quartz boat, stay in the packing-like stainless steel for 90s, and after generating fully cracked substances, pass through the packing-like stainless steel, and react with copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0166] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0167] Example 9
[0168] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0169] Weigh 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm, mix them and put them into a quartz boat, put a stainless steel hollow tube into the middle of the quartz boat, put the quartz boat into the reaction chamber of a vacuum tube furnace, provide a rectangular cover plate of stainless steel, the side of the rectangular cover plate of stainless steel has holes, and cover the rectangular cover plate of stainless steel on the opening of the quartz boat;
[0170] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0171] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the rectangular cover stainless steel, stay for 90s, and generate fully cracked substances, which overflow from the holes on the side and react with the copper powder. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0172] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0173] Example 10
[0174] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0175] Weigh 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm, mix them and put them into a stainless steel boat, put a stainless steel hollow tube into the middle position of the stainless steel boat, put the stainless steel boat into the reaction chamber of a vacuum tube furnace, provide a rectangular cover plate of stainless steel, the side of the rectangular cover plate stainless steel has holes, and cover the rectangular cover plate stainless steel on the opening of the stainless steel boat;
[0176] The reaction chamber was evacuated to 9.9 x 10 -3kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0177] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the rectangular cover stainless steel, stay for 90s, and generate fully cracked substances, which overflow from the holes on the side and react with the copper powder. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0178] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0179] Embodiment 11
[0180] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0181] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm are weighed, mixed and loaded into a quartz boat, a plate-shaped stainless steel is provided, and the interval between adjacent plate-shaped iron-carbon alloys is 50 mm, and the interval is set upstream of the quartz boat, and the plate-shaped stainless steel and the quartz boat are both located in the reaction chamber of a vacuum tube furnace;
[0182] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0183] The gas source is turned on to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the plate-shaped stainless steel from the end of the plate-shaped stainless steel away from the quartz boat, stay in the plate-shaped stainless steel for 20 seconds, and after generating fully cracked substances, pass through the plate-shaped stainless steel, and react with copper powder in the quartz boat. The reaction lasts for 2 hours, so that the surface of the copper powder grows to form a graphene film;
[0184] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0185] Example 12
[0186] This embodiment provides a composite conductor material, and the preparation method thereof is as follows:
[0187] 5 kg of copper powder with a particle size of 1 μm and 4 kg of magnesium oxide with a particle size of 1 μm were weighed, mixed and loaded into a quartz boat, a tubular stainless steel with an inner diameter of 60 mm was provided, and stacked and arranged upstream of the quartz boat, and both the tubular stainless steel and the quartz boat were located in a reaction chamber of a vacuum tube furnace;
[0188] The reaction chamber was evacuated to 9.9 x 10 -3 kPa, introduce 1000sccm of argon until the pressure in the reaction chamber is 101.3kPa, open the exhaust valve of the vacuum tube furnace to make the reaction chamber filled with argon, and heat the reaction chamber at a rate of 20℃ / min until the temperature in the reaction chamber reaches 970℃.
[0189] Open the gas source to introduce CH4 and H2, wherein the volume flow rate of CH4 is 250sccm, and the volume flow rate of H2 is 1000sccm. CH4 and H2 enter the preheating zone, are preheated to 850°C, enter the tubular stainless steel from the end of the tubular stainless steel away from the quartz boat, stay in the tubular stainless steel for 180s, and after generating fully cracked substances, pass through the tubular stainless steel, and react with copper powder in the quartz boat. The reaction lasts for 2h, so that the surface of the copper powder grows to form a graphene film;
[0190] The CH4 and H2 gas sources were turned off, and the reaction chamber was cooled to room temperature to obtain a copper-based graphene composite material.
[0191] Comparative Example 1
[0192] This comparative example is basically the same as Example 1, except that no stainless steel tube is provided in this comparative example, and CH4 directly deposits graphene on the surface of copper powder to obtain a composite conductor material.
[0193] Comparative Example 2
[0194] This comparative example is basically the same as Example 2, except that no stainless steel tube is provided in this comparative example, and CH4 directly deposits graphene on the surface of nickel powder to obtain a composite conductor material.
[0195] Device Example 1
[0196] Device Example 1 provides an electrical contact point, and the composite conductor material prepared in Example 1 is subjected to pressing, sintering, rolling, extrusion, and stamping to obtain the electrical contact point.
[0197] Device Examples 2 to 12
[0198] Device Examples 2 to 12 are substantially the same as Device Example 1, except that in Device Examples 2 to 12, the composite conductor material of Example 1 is replaced by the composite conductor material of Examples 2 to 12, respectively.
[0199] Device Comparison Examples 1 to 2
[0200] Device comparative examples 1-2 are substantially the same as device embodiment 1, except that, in device comparative examples 1-2, the composite conductor material of embodiment 1 is replaced by the composite conductor material of comparative examples 1-2, respectively.
[0201] The cross section of the electrical contact point prepared in device embodiment 1 is scanned by electron microscope to obtain the microstructure of the electrical contact point in device embodiment 1 as shown in FIG. Figure 7 shown.
[0202] Depend on Figure 7 It can be seen that by adopting the copper-based graphene composite conductor material prepared by the scheme of Example 1 to prepare the electrical contact points, in the electrical contact points, the graphene forms a uniform thin film on the copper-based surface, and the graphene has large crystal domains and few grain boundaries, which is beneficial to improving the electrical and thermal conductivity of copper and ensuring the excellent performance of the electrical contact points.
[0203] A current source was connected to the electrical contact points of device embodiments 1 to 12 and device comparative examples 1 to 2 and both ends of pure copper and pure nickel to measure the resistivity of the electrical contact points and pure copper and pure nickel; a heat flow method thermal conductivity instrument was used to measure the thermal conductivity of the electrical contact points of device embodiments 1 to 12 and device comparative examples 1 to 2 and pure copper and pure nickel. The results are shown in Table 1.
[0204] Table 1
[0205] Electrical contact elements Resistivity (Ω·cm) Thermal conductivity (w / m·k) Device Example 1 <![CDATA[1.5×10 -6 ]]> 412 Device Example 2 <![CDATA[1.6×10 -6 ]]> 123 Device Example 3 <![CDATA[1.98×10 -6 ]]> 345 Device Example 4 <![CDATA[1.46×10 -6 ]]> 426 Device Example 5 <![CDATA[1.52×10 -6 ]]> 410 Device Example 6 <![CDATA[1.44×10 -6 ]]> 431 Device Example 7 <![CDATA[1.39×10 -6 ]]> 427 Device Example 8 <![CDATA[1.46×10 -6 ]]> 425 Device Example 9 <![CDATA[1.51×10 -6 ]]> 416 Device Example 10 <![CDATA[1.43×10 -6 ]]> 419 Device Example 11 <![CDATA[1.47×10 -6 ]]> 414 Device Example 12 <![CDATA[1.36×10 -6 ]]> 418 Device Comparison Example 1 <![CDATA[1.69×10 -6 ]]> 404 Device Comparison Example 2 <![CDATA[5.72×10 -6 ]]> 106 Pure Copper <![CDATA[1.75×10 -6 ]]> 397 Pure Nickel <![CDATA[6.84×10 -6 ]]> 82.9
[0206] From Table 1, we can see that:
[0207] It can be seen from the results of device embodiment 1, device embodiments 4-12, device comparative example 1, and pure copper that the thermal conductivity and electrical conductivity of the copper-based metal can be effectively improved by depositing graphene on the copper-based metal; compared with pure copper and the traditional method of directly depositing graphene on the copper-based metal using a carbon source gas, the electrical contact points prepared by the scheme provided in the present application have larger graphene domains, fewer grain boundaries and carbon impurities, and better thermal conductivity and electrical conductivity of the copper-based metal;
[0208] It can be seen from the results of device example 2, device comparative example 2, and pure nickel that the thermal conductivity and electrical conductivity of nickel-based metals can be effectively improved by depositing graphene on nickel-based metals; compared with pure nickel and the traditional method of directly depositing graphene on nickel-based metals using carbon source gas, the electrical contact points prepared by the scheme provided in the present application significantly improve the thermal conductivity and electrical conductivity of nickel-based metals;
[0209] It can be seen from the results of device embodiments 1-3, device comparison examples 1-2, and pure nickel and pure copper that depositing graphene on copper-nickel alloy can effectively improve the thermal conductivity and electrical conductivity of copper-nickel alloy. The copper-nickel alloy electrical contact points prepared by the scheme provided in the present application have electrical conductivity and thermal conductivity between pure copper and pure nickel.
[0210] The preparation method and preparation device of the composite conductor provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technicians in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a composite conductor material, characterized in that: include: Providing a carbon source gas and an iron-carbon alloy, raising the temperature to a first temperature T1, and maintaining the temperature for a period of time t1, so that the carbon source gas is cracked to obtain a cracking product, and the iron-carbon alloy processes the cracking product to obtain an intermediate gas; A metal substrate is provided, and the metal substrate is placed in the intermediate gas, heated to a second temperature T2, kept at the temperature for a period of time t2, and graphene is grown on the surface of the metal substrate to obtain a composite conductor material.
2. The preparation method according to claim 1, characterized in that The carbon source gas includes one or more of methane, ethylene and acetylene; and / or The volume flow rate of the carbon source gas is 200 sccm to 250 sccm.
3. The preparation method according to claim 1, characterized in that: The iron-carbon alloy includes one or more of stainless steel, low carbon steel and low alloy steel.
4. The preparation method according to claim 1, characterized in that: The material of the metal matrix is a metal single substance or an alloy, the metal single substance includes copper and nickel, and the alloy includes a copper-nickel alloy; and / or The metal matrix is metal powder, and the average particle size of the metal powder is 0.01 μm to 100 μm.
5. The preparation method according to claim 1, characterized in that: The intermediate gas includes C x H y One or more of the following, where 1≤x≤2, 0≤y≤4.
6. The preparation method according to claim 1, characterized in that: The first temperature T1 is 800° C. to 1020° C.; and / or The heating rate of heating to the first temperature T1 is 10°C / min to 20°C / min; and / or The time t1 is 20s to 180s.
7. The preparation method according to claim 1, characterized in that: The second temperature T2 is 950°C to 1070°C; and / or The heating rate of heating to the second temperature T2 is 10°C / min to 20°C / min; and / or The time t2 is 1.5h to 2h.
8. The preparation method according to claim 1, characterized in that: The carbon source gas also includes a carrier gas, and the carrier gas includes one or more of hydrogen, ammonia, and nitrogen; the volume flow rate of the carrier gas is 800 sccm to 1000 sccm.
9. The preparation method according to claim 1, characterized in that: Providing the metal matrix also includes providing an anti-sintering agent, which includes one or more of magnesium oxide, aluminum oxide, graphite, chromium, and silver; the anti-sintering agent is an anti-sintering agent powder, and the average particle size of the anti-sintering agent powder is 0.1μm to 15μm; the mass ratio of the metal matrix and the anti-sintering agent is (5 to 10):
4.
10. The preparation method according to claim 1, characterized in that: The iron-carbon alloy is used to treat the cracking product in a first inert atmosphere, the pressure of the first inert atmosphere is 100 kPa to 103 kPa; the volume flow rate of the inert gas in the first inert atmosphere is 700 sccm to 1000 sccm; the inert gas in the first inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon; and / or The growth of graphene on the surface of the metal substrate is carried out in a second inert atmosphere, and the pressure of the second inert atmosphere is 100kPa~103kPa; the volume flow rate of the inert gas in the second inert atmosphere is 700sccm~1000sccm; the inert gas in the second inert atmosphere includes one or more of nitrogen, argon, helium, neon, krypton, xenon, and radon.
11. A preparation device for implementing the preparation method according to any one of claims 1 to 10, characterized in that: include: A first reaction chamber and a second reaction chamber connected to the first reaction chamber, the first reaction chamber contains an iron-carbon alloy, the second reaction chamber contains a metal matrix, and the structure of the iron-carbon alloy is connected so that the carbon source gas can pass into the second reaction chamber after reacting with the iron-carbon alloy to react with the metal matrix.
12. The preparation device according to claim 11, characterized in that: The preparation device further comprises a gas input device located upstream of the first reaction chamber, for inputting a carbon source gas.
13. The preparation device according to claim 11, characterized in that: Along the horizontal direction, the first reaction chamber and the second reaction chamber have a left-right structure, and the iron-carbon alloy is filled and arranged in the first reaction chamber.
14. The preparation device according to claim 13, characterized in that: The first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a filled filler-like iron-carbon alloy, the particle size of the filler-like iron-carbon alloy is 50 mesh to 400 mesh, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
15. The preparation device according to claim 13, characterized in that: The first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a stacked tubular iron-carbon alloy with an inner diameter of 50 μm to 100 mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
16. The preparation device according to claim 13, characterized in that: The first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a plate-shaped iron-carbon alloy placed at intervals, the spacing between adjacent plate-shaped iron-carbon alloys is 1mm to 100mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
17. The preparation device according to claim 13, characterized in that: The first reaction chamber is located on the left side of the second reaction chamber, the iron-carbon alloy is a mesh iron-carbon alloy, the mesh size of the mesh iron-carbon alloy is 50 μm to 100 mm, and the carbon source gas is introduced from the side of the first reaction chamber away from the second reaction chamber.
18. The preparation device according to claim 11, characterized in that: In the vertical direction, the first reaction chamber and the second reaction chamber have an up-and-down structure.
19. The preparation device according to claim 18, characterized in that: The first reaction chamber is located on the upper side of the second reaction chamber, the iron-carbon alloy is a cover plate with holes on the plate surface, the second reaction chamber has an opening, the iron-carbon alloy covers the opening, and the carbon source gas is introduced from the side of the iron-carbon alloy away from the second reaction chamber.
20. The preparation device according to claim 11, characterized in that: The first reaction chamber and the second reaction chamber have an inner and outer structure, the absolute value of the inner diameter difference between the first reaction chamber and the second reaction chamber is ≥5mm, the iron-carbon alloy is tubular, and the wall thickness of the iron-carbon alloy is 3mm to 9mm.
21. The preparation device according to claim 20, characterized in that: The first reaction chamber is located inside the second reaction chamber, the iron-carbon alloy is located in the second reaction chamber, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the end face of the iron-carbon alloy.
22. The preparation device according to claim 20, characterized in that: The first reaction chamber is located outside the second reaction chamber, the iron-carbon alloy is located inside the first reaction chamber, the iron-carbon alloy is a cylinder with holes on the side, and the carbon source gas is introduced from the outer side of the iron-carbon alloy away from the second reaction chamber.